2019
DOI: 10.17159/2519-0105/2019/v74no6a2
|View full text |Cite
|
Sign up to set email alerts
|

The antibacterial effect of herbal alternatives, Triphala and Turmeric, on Enterococcus faecalis - an in vitro study

Abstract: Disinfection and shaping of the canal with a combination of chemical agents and endodontic instruments play important roles in the success of endodontic therapy. Root canal irrigants aid in achieving disinfection in canal systems inaccessible to biomechanical preparation. A wide variety of synthetic irrigants are available today but some may be ineffective, and there may be safety concerns and side effects. Herbal alternatives may be advantageous. To evaluate the antibacterial properties of herbal extracts, na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
1
0
5
Order By: Relevance
“…Triphala showed increased effectiveness in microbial decrease in the root canal, according to Divya S et al [38] Karan Bhargava et al [39] Triphala was found to be more effective against endodontic bacteria. This is owing to its formulation, which contains equal amounts of three different ayurvedic botanicals.…”
Section: As An Antimicrobial Agentmentioning
confidence: 99%
“…Triphala showed increased effectiveness in microbial decrease in the root canal, according to Divya S et al [38] Karan Bhargava et al [39] Triphala was found to be more effective against endodontic bacteria. This is owing to its formulation, which contains equal amounts of three different ayurvedic botanicals.…”
Section: As An Antimicrobial Agentmentioning
confidence: 99%
“…10 Choudhary et al pada tahun 2018 menggunakan 84 gigi permanen manusia dengan akar tunggal yang telah didekoronasi sehingga didapatkan panjang akar 11 mm. 18 Thomas et al pada tahun 2017 menggunakan 49 gigi manusia berakar tunggal yang telah didekoronasi sampai ke cemento enamel junction, kemudian dilakukan preparasi akses. 15 Srikumar et al pada tahun 2020 menggunakan 140 gigi premolar mandibula manusia dengan akar tunggal yang telah didekoronasi hingga cemento enamel junction sehingga didapatkan panjang akar yang seragam sekitar 12 mm.…”
Section: Hasil Dan Pembahasan Metodologi Penelitian Untuk Menguji Pot...unclassified
“…Mayoritas peneliti menggunakan media Blood agar medium. 10,17,18,19 Namun, beberapa peneliti lain ada yang menggunakan metode…”
Section: Hasil Dan Pembahasan Metodologi Penelitian Untuk Menguji Pot...unclassified
See 2 more Smart Citations